Influence of a boiling water treatment on the electrochemical properties of a sol–gel film on AA1050. (November 2015) - Fedel, M.; Deflorian, F.
Abstract : Many studies report that a very simple strategy to improve the corrosion resistance of aluminium is to promote the formation of a pseudo-boehmite (Al2 O3 ·H2 O) layer by a hydrothermal process (i.e. immersion in boiling water). In this work the effect on AA1050 panels of different durations of a boiling water treatment was investigated. In particular, the work is focussed on the corrosion protection properties of a sol–gel layer further applied to the treated aluminium panels and its interaction with the underlying pseudo-bohemite layer. Films consisting of 1:1 molar ratio of 3-glycidoxypropyltrime-thoxysilane (GLYMO) and methyltriethoxysilane (MTES) were applied on AA1050 plates. For this purpose, the effect of the different periods of immersion in boiling water was investigated in terms of morphology by means of scanning electron microscope, in terms of surface chemistry by means of FT-IR and in terms of electrochemical activity of the surface by exploiting electrochemical techniques such as polarisation curves.